2009
DOI: 10.5051/jkape.2009.39.s.239
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effects of modified full-mouth disinfection in the treatment of moderate to severe chronic periodontitis patients

Abstract: Purpose: Full-mouth disinfection enables to reduce the probability of cross contamination from untreated pockets to treated ones, for completing the entire SRP under local anesthesia with chlorhexidine as a mouth wash in two visits within 24 hours. This study aimed to compare the clinical effects of modified full-mouth disinfection (Fdis) after 6 months with those of conventional SRP (cSRP). Methods: Thirty non-smoking chronic periodontitis subjects were randomly allocated two groups. The Fdis group underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Considering the chosen subgingival debridement method (quadrant-wise), it can be said that numerous studies have shown that there are similar clinical outcomes when it comes to the choice of scaling and the SRP treatment method (quadrant-wise or full-mouth), as long as the procedure is performed correctly [ 31 , 32 , 33 , 34 ]. Additionally, microbiological studies conducted after evaluating both techniques also supported the same conclusions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the chosen subgingival debridement method (quadrant-wise), it can be said that numerous studies have shown that there are similar clinical outcomes when it comes to the choice of scaling and the SRP treatment method (quadrant-wise or full-mouth), as long as the procedure is performed correctly [ 31 , 32 , 33 , 34 ]. Additionally, microbiological studies conducted after evaluating both techniques also supported the same conclusions [ 35 ].…”
Section: Discussionmentioning
confidence: 99%